2018
DOI: 10.3389/fimmu.2018.02875
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant BCG Vaccines Reduce Pneumovirus-Caused Airway Pathology by Inducing Protective Humoral Immunity

Abstract: The Human Respiratory Syncytial Virus (hRSV) and the Human Metapneumovirus (hMPV) are two pneumoviruses that are leading agents causing acute lower respiratory tract infections (ALRTIs) affecting young infants, the elderly, and immunocompromised patients worldwide. Since these pathogens were first discovered, many approaches for the licensing of safe and effective vaccines have been explored being unsuccessful to date. We have previously described that immunization with recombinant strains of Mycobacterium bov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 55 publications
4
76
0
Order By: Relevance
“…The Netherlands and Germany show a significant increase in their confirmed cases per million inhabitants, suggesting that the contagion curve will increase similar to the Italian, Spanish, and American ones. A common feature of these countries is that they do not include BCG in their national vaccination programs, so we speculate that this vaccine may have a protective role in the immune defense against respiratory diseases (36)(37)(38)(39)(40)(41). Utilizing the WHO immunization monitoring data (9), we elaborated the graphs shown in Figures 2B-D comparing the contagion and mortality rates due to COVID-19 between countries with or without administration of BCG in their national vaccination programs.…”
Section: Trained Immunity As a Strategy Against Sars-cov-2mentioning
confidence: 99%
“…The Netherlands and Germany show a significant increase in their confirmed cases per million inhabitants, suggesting that the contagion curve will increase similar to the Italian, Spanish, and American ones. A common feature of these countries is that they do not include BCG in their national vaccination programs, so we speculate that this vaccine may have a protective role in the immune defense against respiratory diseases (36)(37)(38)(39)(40)(41). Utilizing the WHO immunization monitoring data (9), we elaborated the graphs shown in Figures 2B-D comparing the contagion and mortality rates due to COVID-19 between countries with or without administration of BCG in their national vaccination programs.…”
Section: Trained Immunity As a Strategy Against Sars-cov-2mentioning
confidence: 99%
“…In a recent study, rBCG- N -hRSV which expresses the nucleoprotein (N) of the human respiratory syncytial virus (hRSV), protected mice from hRSV challenge by induction of hRSV specific neutralizing antibodies and reduced the clinical pathology of the lung [57] .…”
Section: Bcg: An Attractive Vector For Recombinant Vaccinesmentioning
confidence: 99%
“…A similar induction of serum neutralizing antibodies was observed with a cold-passage/stabilized RSV containing several attenuating point mutations as well as deletion of the small hydrophobic (SH) protein (RSVcps2) ( 21 ). Finally, preclinical studies of a recombinant BCG vaccine expressing the RSV nucleoprotein (N) demonstrated an effective cellular and humoral immune response in mice ( 22 25 ).…”
Section: Rsv Vaccine Modalities and Lessons From The Host Immune Respmentioning
confidence: 99%
“…One of the most common viral targets for antibodies is the RSV fusion (F) protein ( 38 , 39 ). Vaccine formulations containing the N protein also induce long-lasting neutralizing antibodies and could serve as a novel antiviral target ( 22 , 25 ). The RSV G protein is involved in the initiation of the virus life cycle and has a potent effect on the regulation of the immune response ( 36 ).…”
Section: Rsv Vaccine Modalities and Lessons From The Host Immune Respmentioning
confidence: 99%